Clinical Experiences and Mechanism of Action with the Use of Oxytocin Injection at Parturition in Domestic Animals: Effect on the Myometrium and Fetuses - Míriam Marcet-Rius; Cécile Bienboire-Frosini; Karina Lezama-García; Adriana Domínguez-Oliva; Adriana Olmos-Hernández; Patricia Mora-Medina; Ismael Hernández-Ávalos; Alejandro Casas-Alvarado; Angelo Gazzano (Animals, 2023)
Oxytocin is a key hormone for parturition and maternal traits in animals. During the peripartum period, the levels of endogenous oxytocin dictate physiological events such as myometrial contractions, prostaglandin production with the subsequent increase in oxytocin receptors, and the promotion of lactation when administered immediately after birth. While this hormone has some benefits regarding these aspects, the exogenous administration of oxytocin has been shown to have detrimental effects on the fetus, such as asphyxia, meconium staining, ruptured umbilical cords, and more dystocia cases in females. This review aims to analyze the main effects of oxytocin on myometrial activity during parturition, and its potential favorable and negative administration effects reflected in the fetus health of domestic animals. In conclusion, it is convenient to know oxytocin’s different effects as well as the adequate doses and the proper moment to administrate it, as it can reduce labor duration, but it can also increase dystocia.